La borne milliaire de Vollore-Ville (Puy-de-Dôme), forme et transformation - Jean-Claude Béal (Revue Archéologique du Centre de la France)
The Vollore-Ville milestone Vollore City was considered a unique monument which, over an above its function as an indicator of distance from the capital of the Arverni, also signalled the boundary between the provinces of Aquitaine and Lyonnaise. A review of the preserved evidence shows in fact the need to distinguish two states. This is primarily a milestone of a type also known through three other Arvernian markers, and whose adoption was without doubt to celebrate the prince. It is then a “croix à bubons” associated with Christian rites to protect against the plague. Broken up during the French Revolution, the monument became the subject of a “restoration” policy in 1848.